SINFONIA: Gerenciamento Seguro de Funções Virtualizadas de Rede através de Corrente de Blocos - Rebello, Gabriel Antonio Fontes; Alvarenga, Igor Drummond; Automação, Grupo de Teleinformática e (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2018: Anais do I Workshop em Blockchain: Teoria, Tecnologias e Aplicações, 2018)
Network Function Virtualization (NFV) technology provides a flexible and low-cost network model that replaces proprietary hardware network functions with software-based virtualized network functions which run on general-purpose machines. Virtual functions are orchestrated in a distributed multi-tenant trustless environment and are, thus, susceptible to security threats. This article proposes SINFONIA, a blockchain-based system that provides security to virtualized networks, ensuring auditability, non-repudiation, and integrity of orchestration operations. SINFONIA provides a modular architecture which allows the orchestration of network functions in a simple and agile way. A prototype for the Open Platform for Network Function Virtualization (OPNFV) was developed with the implementation of a specific blockchain and a collusion-resistant consensus protocol. The results show that SINFONIA provides security with low overhead to the cloud orchestrator with stable performance as the number of consensus participants increases.